Academic perspectives in a prison health care setting (Research, Society and Development, 2022)
Objective: To report the experience of nursing students in a context of male relationships in a penitentiary complex. Methods: Study of the type experience report, about the academic perceptions when experiencing a scenario of deprivation of freedom in a Penitentiary Complex, from the perspective of masculinities. The students followed the routine of men deprived of liberty, prison security agents and health professionals who work in this space. The immersion took place between the years 2018 and 2019, over a period of 12 months. Results: Prior to the immersion of the academics, a weekly study of theoretical preparation was carried out on masculinities, medical anthropology, men's health and on the context of deprivation of liberty. In the field, the educational groups of the National Program for Access to Technical Education and Employment and the Youth and Adult Education Program were used to access the inmates, while the prison security agents and health professionals were accompanied in their sectors. A field diary was started, in which all the academic experiences and perceptions with this public were transcribed. Final Considerations: It was verified how difficult nursing care works in unique contexts, and how this process still needs to be improved for publics and scenarios of greater vulnerability, to then achieve an egalitarian health.